Analyzing irrational purchase decision on aesthetic packaging: the moderating role of emotional appeal / Geetha Muthusamy, Roszi Naszariah Nasni Naseri and Wan Kalthom Yahya - Muthusamy, Geetha; Naseri, Roszi Naszariah Nasni; Yahya, Wan Kalthom (Faculty of Art and Design, 2024)
This conceptual paper examines how aesthetic packaging affects the purchase decisions of cosmetic products through the Theory of Planned Behavior (TPB) model, irrational factors. The TPB model, comprising Attitude, Subjective Norms, and Perceived Behavioral Control, serves as the analytical framework for consumer behavior. The central issue lies in understanding the influence of packaging aesthetics on decisions, particularly the irrational aspects such as emotional appeal. Emotional appeal is hypothesized to act as a moderating factor, potentially amplifying the perceived value of aesthetically pleasing packaging and leading to less rational purchasing decisions. The methodology includes a purposive sampling of cosmetic product consumers, with the sample size determined using G*Power. Data analysis will be conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). This study seeks to uncover the impact of emotional appeal on packaging aesthetics, providing insights to improve marketing strategies and packaging designs within the cosmetic industry.